Prussian blue / chitosan / sodium alginate composite hydrogel and its preparation method and application
By developing Prussian blue chitosan compound hydrogel loaded with doxorubicin and combined with photothermal therapy, the problems of poor selectivity, high toxicity and strong drug resistance in breast cancer treatment were solved, and efficient and selective tumor treatment and inhibition of lung metastasis were achieved.
Patent Information
- Application Number
- CN202211342729.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-28
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-10-28
AI Technical Summary
The existing breast cancer treatment methods have problems such as poor selectivity, high toxicity and strong drug resistance. Single chemotherapy or photothermal treatment is difficult to effectively eliminate tumors, and mild photothermal treatment is not effective.
A Prussian blue chitosan composite hydrogel was developed to polymerize Prussian blue in situ through chitosan and complex with oxidized sodium alginate to form a composite hydrogel cross-linked imine bonds, loaded with antitumor drugs such as doxorubicin, and combined with photothermal therapy.
It has achieved the improvement of drug selectivity and efficacy in breast cancer treatment, reduce toxic and side effects, prolong the drug action time, enhance bioavailability, and effectively inhibit tumor growth and metastasis.
Smart Images

Figure CN115651220B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to a Prussian blue chitosan composite hydrogel and its preparation and application in preparing a drug system for treating breast cancer. Background Art
[0002] According to the latest "2020 Global Cancer Report", breast cancer has become a commonly diagnosed cancer in women and is also the leading cause of cancer death in women worldwide. Therefore, it is an international problem that needs to be solved urgently to study new methods and treatment strategies to improve the treatment and diagnosis of breast cancer, reduce the incidence and mortality of breast cancer, and prolong the survival of patients. Studies have shown that single chemotherapy drugs, such as doxorubicin (DOX), are difficult to completely eliminate tumors due to their low selectivity and non-targeted nature. In addition, long-term use can also induce multidrug resistance in cancer cells. Photothermal therapy (PTT), as a non-invasive treatment method with low toxicity and high selectivity, provides a new strategy for the treatment of breast cancer. However, single PTT for photothermal tumor ablation relies on excessive heat, which can damage surrounding normal tissues, while mild PTT tumor photothermal ablation has reduced effects. Therefore, the combination of mild PTT and chemotherapy for anti-tumor treatment has become a new option.
[0003] Prussian blue nanoparticles (PB NPs) are composed of a simple ferrocyanide-ferrous (Fe 3+ -CN-Fe 2+ ) has excellent photothermal conversion ability and biocompatibility, and the US FDA has certified that it is harmless to the human body when taken orally. Among the many drug carriers, hydrogel is one of the important drug delivery platforms due to its sensitivity to environmental stimuli, high swelling capacity, permeability and similarity to human tissue. Hydrogels and encapsulated drugs have multiple interactions, ensuring that the release of various drugs can be controlled in time and space. The clinical manifestations of breast cancer are high incidence, high metastasis rate and high mortality rate. At the same time, metastasis is the main cause of death for more than 90% of breast cancer patients. Single treatments such as chemotherapy and photothermal therapy have their limitations. Summary of the invention
[0004] In order to solve the above problems involved in the prior art, the present invention provides a Prussian blue chitosan composite hydrogel, wherein the Prussian blue chitosan composite hydrogel is composed of chitosan, Prussian blue, sodium alginate and the like as raw materials, the polysaccharide component chitosan is modified and Prussian blue is polymerized in situ to obtain polyaldehyde sodium alginate, and the imine bond cross-linked composite hydrogel is obtained by changing the concentration and volume of Prussian blue chitosan and oxidized sodium alginate.
[0005] The preparation method of the Prussian blue / chitosan / sodium alginate composite hydrogel of the present invention comprises the steps of in-situ polymerization of Prussian blue by chitosan and the step of compounding sodium alginate. Preferably, the step of in-situ polymerization of Prussian blue by chitosan is to first modify chitosan by carboxyethylation, and then in-situ polymerize the chitosan macromolecular chain segments to generate Prussian blue. In the present invention, chitosan needs to be modified because ordinary chitosan can only be dissolved under acidic conditions due to the characteristics of the molecular chain segments themselves, resulting in its inability to be used under physiological conditions. However, through the carboxyethylation of the present invention, it can be quickly dissolved at physiological pH values.
[0006] As a further preferred embodiment, the step of in-situ polymerization of Prussian blue by chitosan comprises: suspending 3-6 g of chitosan in 100-300 mL of deionized water, adding 5-6 mL of acrylic acid, and magnetically stirring at 40-60° C. for 2-5 days; adjusting the pH to 10.0-12.0, dialyzing with deionized water, and the dialyzed molecular weight Mw=6-8KD; freeze-drying to obtain carboxyethyl chitosan; preparing a hydrochloric acid solution of carboxyethyl chitosan, adding a hydrochloric acid solution of potassium ferrocyanide, heating at 60-80° C. to adjust the pH to 9.0-11.0, dialyzing with deionized water, and the dialyzed molecular weight Mw=6-8KD; and freeze-drying to obtain a modified Prussian blue / chitosan complex.
[0007] In a further embodiment, the step of in-situ polymerization of Prussian blue by chitosan comprises the following steps:
[0008] (1) Weigh 4 g of chitosan and suspend it in 200 mL of deionized water. Add 5.84 mL of acrylic acid and stir under magnetic stirring at 50 °C for 3 days.
[0009] (2) Adjust the pH to 10.0-12.0 with 1 mol / L sodium hydroxide solution and dialyze with deionized water for 3 days (Mw = 6-8 KD);
[0010] (3) The dialyzed solution was freeze-dried to obtain carboxyethyl chitosan (CEC); 5.0 mL of 2 wt% carboxyethyl chitosan hydrochloric acid solution was prepared, 2.5 mL of hydrochloric acid solution containing 0.5 wt% potassium ferrocyanide was added, vortexed and mixed, and heated in a 70°C constant temperature electric heating box for 4 h, and then the pH was adjusted to 9.0-11.0, and dialyzed against deionized water for 3 d (Mw=6-8KD); the concentration of hydrochloric acid used was 6-7 wt%;
[0011] (4) The dialyzed solution was freeze-dried to obtain a modified Prussian blue / chitosan complex.
[0012] As a preferred embodiment, in the step of compounding sodium alginate, sodium alginate is made into polyaldehyde sodium alginate, and then the Prussian blue / chitosan complex obtained in the previous step is compounded with the polyaldehyde sodium alginate to obtain an imine-bonded cross-linked Prussian blue / chitosan / sodium alginate composite hydrogel; the polyaldehyde sodium alginate is oxidized sodium alginate, and the preparation of oxidized sodium alginate adopts conventional methods such as oxidation reaction of sodium alginate with sodium periodate in ethanol / water solvent to obtain it, and the oxidation degree of the aldehyde group is preferably adjusted to 40%-60%. If the oxidation degree is too low, the cross-linking is insufficient, and if the oxidation degree is too high, the component toxicity is too high, which affects its further application in vivo.
[0013] In a more preferred embodiment, the present invention compounds 3-5wt% of Prussian blue / chitosan complex with 4-6wt% of oxidized sodium alginate at a volume ratio of 1-2:1-2 to obtain a composite hydrogel with a solid content of 7-11wt%. More preferably, the present invention compounds 4wt% of Prussian blue / chitosan complex with 5wt% of oxidized sodium alginate at a volume ratio of 1:1 to obtain a Prussian blue / chitosan / sodium alginate composite hydrogel with a solid content of 9wt%, which has a porous network structure with a pore size of 50-150μm. The internal microscopic morphology of the gel can be observed by scanning electron microscopy. The three-dimensional porous structure and high water content of the hydrogel can provide an adaptive 3D microenvironment for cell proliferation, and can also load drugs and be used as an implantable biomedical material.
[0014] The composite hydrogel of the present invention can be used as a drug-carrying platform for drug encapsulation, such as in the preparation of a drug system for treating cancer such as breast cancer. The hydrogel system of the present invention achieves a better purpose of treating tumors by encapsulating anti-tumor and antibacterial drugs and combining them with photothermal therapy.
[0015] The present invention obtains Prussian blue / chitosan / sodium alginate composite hydrogels with different imine bond crosslinking degrees by adjusting the concentration and / or volume of Prussian blue / chitosan and oxidized sodium alginate. Rheological detection shows that the gelation time of the Prussian blue chitosan composite hydrogel is most suitable when the solid content is 9wt%, and it can be quickly transformed from a solution state to a gel state. Combined with self-healing and injectable macroscopic experiments, it can be seen that the hydrogel has good injectability and self-healing properties, and can be applied to clinical treatment. Even if the structure is destroyed after injection, it can still heal in a relatively short time. Photothermal experiments show that the composite gel of Prussian blue chitosan and oxidized sodium alginate with a solid content of 9wt% has good thermal conductivity and can be applied to multiple biomedical fields such as tumor imaging and nuclear magnetic resonance technology.
[0016] The invention obtains Prussian blue chitosan composite hydrogels with different proportions by mixing a Prussian blue chitosan solution and an oxidized sodium alginate solution in different proportions.
[0017] The present invention uses Prussian blue modified chitosan and polyaldehyde sodium alginate to undergo Schiff base reaction to produce dynamic imine bond cross-linking to prepare tumor microenvironment acid response hydrogel, and loads doxorubicin, and then supplements with a combined treatment scheme of photothermal therapy, which can be used to effectively treat breast cancer. The slightly acidic environment of the tumor area and the photothermal response are combined with controllable drug release to achieve the construction of a "smart responsive" hydrogel carrier.
[0018] The present invention uses a hydrogel chemotherapy-photothermal combined treatment, and on the basis of reliable biosafety at the cell and animal levels, respectively, the migration inhibition of 4T1 cells, free radical scavenging, and animal grouping treatment experiments prove the efficacy of the combined treatment and the ability to inhibit lung metastasis of tumor tissue. The combined treatment of the hydrogel-loaded doxorubicin assisted by photothermal therapy of the present invention can be injected non-invasively into the lesion (no surgery or minimally invasive treatment is required, and it can be injected directly with a needle), while maintaining the drug concentration in the tumor site for a long period of time, improving the bioavailability of the drug, and increasing the degree of T cell infiltration in the tumor site of patients with low immunogenic tumors, thereby improving the efficacy of the drug, and minimizing toxic side effects, decomposing endogenous H2O2 into O2, alleviating the hypoxic tumor microenvironment, and releasing the anticancer drug DOX, which is used for effective breast cancer photothermal chemotherapy to achieve the purpose of treatment.
[0019] In addition, the composite hydrogel of the present invention has large stress and strong compression resistance, so that it can be used as a tissue engineering implant material; its injectable property makes it applicable to minimally invasive treatment of wounds in patients in clinical practice, and filling wounds of irregular shapes or narrow places; it has good photothermal conversion efficiency and high photothermal stability, can be reused many times, and has good photothermal treatment effect in clinical treatment; it has certain application potential in biomedical research fields such as drug loading and delivery, hemostasis, and antibacterial, and provides possibilities for the innovation of disease treatment methods and medical materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a microscopic photograph of the Prussian blue chitosan composite hydrogel provided by the present invention.
[0021] Figure 2 The rheological method was used to measure the gelation time of the composite hydrogel.
[0022] Figure 3 Measurement of the photothermal properties of composite hydrogels.
[0023] Figure 4 Photo of the biosafety assessment of hydrogels at the cellular level using the Live / Dead fluorescence method.
[0024] Figure 5 These are the photothermal synergistic chemotherapy effects of each experimental group.
[0025] Figure 6 HE staining images of organs in each group of mice on the 14th day of "treatment" in the safety experiment.
[0026] Figure 7 These are temperature images of the tumors of tumor-bearing mice after irradiation for different time periods.
[0027] Figure 8 This is a line graph of weight gain of mice during the chemotherapy-photothermal combined treatment with the Prussian blue chitosan composite hydrogel of the present invention.
[0028] Fig. 9 It is a quantitative line graph of tumor volume change during chemotherapy-photothermal combined treatment of the Prussian blue chitosan composite hydrogel of the present invention.
[0029] Fig.10 This is the staining of tumor tissues in each group after the chemotherapy-photothermal combined treatment of the Prussian blue chitosan composite hydrogel of the present invention is completed.
[0030] Fig.11 These are photos of the tumors in each group after peeling off after the chemotherapy-photothermal combined treatment with the Prussian blue chitosan composite hydrogel of the present invention was completed.
[0031] Fig.12 This is a statistical graph of tumor weight in each group after the chemotherapy-photothermal combined treatment of the Prussian blue chitosan composite hydrogel of the present invention is completed.
[0032] Fig.13 This is a statistical chart of lung metastasis counts in each group after the chemotherapy-photothermal combined treatment of the Prussian blue chitosan composite hydrogel of the present invention is completed.
[0033] Fig.14 This is the HE staining image of the lungs of each group after the chemotherapy-photothermal combined treatment of the Prussian blue chitosan composite hydrogel of the present invention, and the metastatic lesions are marked with circles. DETAILED DESCRIPTION
[0034] The following embodiments are further descriptions of the content of the present invention as an explanation of the technical content of the present invention, but the essential content of the present invention is not limited to the following embodiments. Ordinary technicians in this field can and should know that any simple changes or replacements based on the essential spirit of the present invention should fall within the scope of protection required by the present invention.
[0035] The hematoxylin-eosin staining method described in the following examples, referred to as HE staining, is one of the commonly used staining methods in paraffin section technology. Hematoxylin staining solution is alkaline, mainly making the chromatin in the cell nucleus and the nucleic acid in the cytoplasm purple-blue; eosin is an acidic dye, mainly making the components in the cytoplasm and extracellular matrix red. H&E staining is the most basic and widely used technical method in the teaching and scientific research of histology, embryology, and pathology.
[0036] The TUNEL staining described in the following examples can detect the breakage of nuclear DNA in cells during apoptosis. The principle is that the labeled (fluorescent or biotin) dUTP can be connected to the 3'-OH end of the broken DNA in apoptotic cells under the action of terminal deoxyribonucleotidyl transferase (Tdl Enzyme), and then the apoptotic cells can be specifically and accurately detected by fluorescence excitation or chemical color development. Normal or proliferating cells have almost no DNA breakage, so no 3'-OH is formed and can rarely be stained. This experiment is suitable for in situ detection of apoptosis in tissue and cell samples.
[0037] The MTT method described in the following examples is also called MTT colorimetry, which is a method for detecting cell survival and growth. Its detection principle is that the succinate dehydrogenase in the mitochondria of living cells can reduce exogenous MTT to water-insoluble blue-purple crystalline formazan and deposit it in the cells, while dead cells do not have this function. Dimethyl sulfoxide (DMSO) can dissolve the formazan in the cells, and its light absorption value is measured at a wavelength of 490nm using an enzyme-linked immunosorbent assay, which can indirectly reflect the number of living cells. Within a certain range of cell numbers, the amount of MTT crystals formed is proportional to the number of cells. This method has been widely used in the activity detection of some biologically active factors, large-scale anti-tumor drug screening, cytotoxicity tests, and tumor radiosensitivity determinations.
[0038] The reactive oxygen fluorescent probe method described in the following examples is a method for detecting reactive oxygen using the fluorescent probe DCFH-DA. DCFH-DA itself has no fluorescence and can freely pass through the cell membrane. After entering the cell, it can be hydrolyzed by the esterase in the cell to generate DCFH. However, DCFH cannot penetrate the cell membrane, so the probe can be easily loaded into the cell. The reactive oxygen in the cell can oxidize the non-fluorescent DCFH to generate fluorescent DCF. The fluorescence of DCF can be detected to know the level of reactive oxygen in the cell.
[0039] Example 1
[0040] The preparation method of modified Prussian blue / chitosan is as follows:
[0041] (1) Weigh 4 g of chitosan and suspend it in 200 mL of deionized water. Add 5.84 mL of acrylic acid and stir under magnetic stirring at 50 °C for 3 days.
[0042] (2) The pH value was adjusted to 10.0-11.0 with 1 mol / L sodium hydroxide solution and dialyzed with deionized water for 3 days (Mw=7KD).
[0043] (3) Freeze-dry the dialyzed solution to obtain carboxyethyl chitosan. Prepare 5.0 mL of 2 wt% carboxyethyl chitosan hydrochloric acid solution, add 2.5 mL of hydrochloric acid solution containing 0.5 wt% potassium ferrocyanide, vortex mix, heat in a 70°C constant temperature electric heating box for 4 h, adjust the pH to 10.0, and dialyze with deionized water for 3 days (Mw = 7KD). The hydrochloric acid concentration used is 6-7 wt%;
[0044] (4) The dialyzed solution was freeze-dried to obtain modified Prussian blue / chitosan particles.
[0045] Example 2
[0046] Preparation of oxidized sodium alginate: Weigh 1.0g of sodium alginate and disperse it in 100mL of ultrapure water, heat it in a water bath at 50℃ with magnetic stirring to dissolve it. Add 0.54g of sodium periodate and stir the reaction for 4h at room temperature in the dark. Then add 1.5mL of ethylene glycol and continue stirring for 1h to terminate the oxidation reaction. The reaction solution is dialyzed with a dialysis bag (molecular weight cutoff of 7KD) for 72h, and the dialysis water is replaced every 6h. After dialysis, the product is freeze-dried in a vacuum to obtain an oxidized sodium alginate yield of 77% and an oxidation degree of 45%.
[0047] The preparation method of Prussian blue / chitosan / oxidized sodium alginate composite hydrogel is as follows:
[0048] On the basis of the modified Prussian blue / chitosan particles obtained in Example 1, the Prussian blue / chitosan solution and the oxidized sodium alginate solution were mixed in different proportions to obtain Prussian blue chitosan composite hydrogels with different ratios: for example, 3wt% of the Prussian blue chitosan solution and 4wt% of the oxidized sodium alginate solution were mixed in a volume ratio of 1:1 to obtain a Prussian blue / chitosan / oxidized sodium alginate composite hydrogel with a solid content of 7wt%; 4wt% of the Prussian blue chitosan solution and 5wt% of the oxidized sodium alginate solution were mixed in a volume ratio of 1:1 to obtain a Prussian blue / chitosan / oxidized sodium alginate composite hydrogel with a solid content of 9wt%; 5wt% of the Prussian blue chitosan solution and 6wt% of the oxidized sodium alginate solution were mixed in a volume ratio of 1:1 to obtain a Prussian blue / chitosan / oxidized sodium alginate composite hydrogel with a solid content of 9wt%.
[0049] The rheological method was used to measure the gelation time of the composite hydrogel. The gelation time of the hydrogel refers to the time required for the sample to transform from the sol state to the gel state, and its length directly affects the injectability of the hydrogel in vivo. Figure 2 As shown in the figure, the gel time of the composite hydrogel made of different concentrations of Prussian blue chitosan and oxidized sodium alginate solution is in the range of 20-90s. In the initial stage of mixing the two components of Prussian blue chitosan solution and oxidized sodium alginate solution, the elastic modulus of the sample is greater than the viscous modulus, and it appears as a viscoelastic liquid. As time goes on, the contribution of the elastic modulus gradually exceeds the contribution of the viscous modulus, and the sample gels, forming a three-dimensional cross-linked network structure throughout the entire system. At this time, the intersection of G' and G" is the gel point (G' is the storage modulus, shown as solid dots in the figure; G" is the energy loss modulus, shown as hollow dots in the figure). The results show that the gel time of the hydrogel with a solid content of 7wt% is between 80-90s, the gel time of the hydrogel with a solid content of 9wt% is between 60-70s, and the gel time of the hydrogel with a solid content of 11wt% is between 20-30s. If the gel time is too long, the application will be affected due to rheology, and if the time is too short, it is easy to solidify prematurely, resulting in problems such as syringe blockage. Therefore, a gelling time that is too long or too short is not conducive to the injection application of the hydrogel. Therefore, the hydrogel with a solid content of 9wt% has an appropriate gelling time and is more suitable for the injection application of the hydrogel, and the mechanical properties are stable after gelling.
[0050] like Figure 3 , at 1.0W / cm 2 , under 5min infrared irradiation, the temperature of the hydrogel samples increased accordingly. The temperature of the hydrogel with a solid content of 7wt% changed to 26°C; the temperature of the hydrogel with a solid content of 9wt% changed to 41°C; the temperature of the hydrogel with a solid content of 11wt% increased by 49°C. In view of further in vivo application, excessive heat will damage the surrounding normal tissues, and too low temperature will not achieve the photothermal treatment effect, so the hydrogel with a solid content of 9wt% is the most suitable.
[0051] Therefore, when 4wt% Prussian blue chitosan solution and 5wt% oxidized sodium alginate solution were mixed in a volume ratio of 1:1 and the solid content was 9wt%, the resulting composite hydrogel had better rheological properties, and the gelation time and photothermal properties were the most suitable. Figure 1As shown, the porous network structure inside the composite gel can be observed, which is conducive to the further application of the composite gel in drug encapsulation and delivery. The composite hydrogel made of Prussian blue chitosan and oxidized sodium alginate is formed by covalent cross-linking of the amino group on the chitosan and the carbonyl group on the polyaldehyde sodium alginate. The Prussian blue chitosan composite hydrogel with a solid content of 9wt% is used, that is, Prussian blue modified chitosan and polyaldehyde sodium alginate undergo Schiff base reaction to produce dynamic imine bond cross-linking to prepare a tumor microenvironment acid-responsive hydrogel, and doxorubicin is loaded, and then supplemented with a combined treatment regimen of photothermal therapy for the effective treatment of breast cancer. Specifically:
[0052] 1. Experimental grouping scheme
[0053] The treatment factors of this study are: Prussian blue hydrogel (PB Gel), doxorubicin (DOX) and near-infrared photothermal irradiation (L). According to the principle of randomized controlled trials, one control group and six experimental groups are considered:
[0054] (1) Phosphate buffered saline (PBS) control group
[0055] (2) Phosphate buffered saline + near-infrared light group (PBS+L)
[0056] (3) Free doxorubicin group (DOX)
[0057] (4) Prussian blue hydrogel group (PB Gel)
[0058] (5) Prussian blue hydrogel loaded with doxorubicin (PB / DOX Gel)
[0059] (6) Prussian blue hydrogel + near-infrared irradiation group (PB Gel+L)
[0060] (7) Prussian blue loaded doxorubicin hydrogel + near-infrared irradiation group (PB / DOX Gel+L).
[0061] Cell and animal experiments were randomly grouped as described above.
[0062] 2. In vitro cell experiments
[0063] (1) The MTT method was used to evaluate the cytotoxicity of the hydrogel precursor.
[0064] Different concentrations of hydrogel precursors Prussian blue chitosan (PBCEC) and oxidized sodium alginate (OSA) (0, 25, 50, 75, 100, 200, 300, 400, 500 μg mL -1 ) were added to the two cells for co-culture. The MTT kit was operated in the standard manner, and the absorbance at 490 nm was tested with an enzyme marker, and the relative survival rate of the cells was calculated.
[0065] (2) Live / Dead fluorescence method was used to determine the biosafety of hydrogels.
[0066] The L929 cell culture medium was replaced with the hydrogel extract and cultured for different time periods. The Calcein-AM / PI live / dead cell staining kit produced by Solebold was then used according to the instructions. Live cells (yellow-green fluorescence) and dead cells (red fluorescence) were observed under an inverted fluorescence microscope at 490 and 545 nm excitation light, respectively.
[0067] (3) The reactive oxygen species fluorescence probe method was used to measure the intracellular reactive oxygen species.
[0068] After L929 cells adhered to the well plate, different concentrations (50, 100, 150 and 200 μg / mL) of PBCEC solution were added to the well plate and co-cultured for 4 hours. Then 800 μM H2O2 was added to each well and co-cultured for 20 hours. Washed three times with PBS, then 500 μL of 10 μM DCFH-DA serum-free cell culture solution was added to each well, incubated in a 37°C incubator for 30 minutes, and then washed three times with PBS to fully remove DCFH-DA that did not enter the cells. The samples were observed under a fluorescence microscope (λex=405nm,λem=480-520nm).
[0069] (4) Photothermal synergistic chemotherapy of cells in vitro.
[0070] 4T1 cells were grouped according to the experimental grouping scheme, and the corresponding culture medium was replaced. The near-infrared light group was treated with light (808 nm, 1 W / cm 2 After incubation for 24 h, each group was stained with Calcein-AM / PI live cell / dead cell double staining kit and observed and photographed under a fluorescent inverted microscope.
[0071] 3. Animal Experiments
[0072] (1) Mouse breeding conditions
[0073] 35-day-old female BALB / c mice (SPF grade) were raised in an SPF grade environment, with the temperature maintained at 22-25°C, the humidity maintained at about 40%, the circadian rhythm maintained at 12h / 12h, and the drinking water, feed and experimental supplies were sterilized. The mice's condition and living environment were observed every 24h, and feed and drinking water were supplemented. The mice were weighed and the data were recorded to confirm that the mice were in good condition. The mouse bedding and mouse cage were replaced every 3 days.
[0074] (2) Chronic toxicity
[0075] After the "treatment" operation of the mice, the weight of each mouse was recorded once every 2 days. On the 14th day of the "treatment", about 0.8 mL of blood was collected from each mouse by eye removal and bleeding, and the mice were killed by cervical dislocation. The blood was centrifuged at 7000r / min for 30 minutes, and the supernatant was taken to obtain a chronic serum sample. The main organs of the mice were collected by dissection: heart, liver, spleen, lung, and kidney, and fixed with 4% paraformaldehyde to obtain organ samples of safety experimental mice. Paraffin sections were made from the organ samples, stained with hematoxylin-eosin (HE) dye, and examined under a microscope.
[0076] (3) Establishment of mouse breast cancer transplant model
[0077] First, 4T1 cells were cultured in vitro for large-scale expansion. 6 hours before tumor implantation, the culture medium was changed to serum-free DMEM culture medium and the cells were starved. 4T1 cells were digested and collected by centrifugation (1000rpm, 4℃, 5min) and counted. 500,000 cells were resuspended in 1×PBS at a density of 50μL and placed on ice. Matrigel was added to make the volume ratio with PBS 1:9. 50μL of the cell mixture was taken and injected subcutaneously into the third pair of mammary fat pads on the right side of the mouse. The tumor volume and mouse weight were measured every 2 days to check the establishment of the model.
[0078] (4) Photothermal therapy in tumor-bearing mice
[0079] On the 7th day of tumor implantation, the mice were divided into 7 groups according to the experimental grouping scheme in 1, with 5 mice in each group. Each group was treated separately: after the model mice were anesthetized, they were subcutaneously injected at the tumor lesion after disinfection with 75% ethanol. The injection dose of all groups was equivalent to 50μL, DOX 1mM, near-infrared irradiation 1.0W / cm 2 , 5min. The temperature of mice in the photothermal therapy group was recorded and photos were taken using a thermal imager. The weight of mice and their tumor volume were recorded every 2 days during the 14 days of treatment.
[0080] (5) Dissection and tumor removal of tumor-bearing mice
[0081] On the 14th day after treatment, the mice bearing tumors were killed by cervical dislocation. The tumor tissues of the tumor-bearing mice were peeled off, and the non-tumor tissues were cut off to obtain tumor samples. The tumors were weighed and photographed. The mice were dissected, the lungs were removed, and fixed with 4% paraformaldehyde to obtain lung samples of the model mice.
[0082] (6) Histological evaluation of tumor growth inhibition in vivo
[0083] The obtained tumor was fixed with 4% paraformaldehyde and paraffin sections were made. Antigen antibody (Ki67 antibody) and TdT-mediated dUTP Nick-End Labeling (TUNEL) detection kit and hematoxylin-eosin (HE) staining were performed according to the instructions of each instrument, and Ki-67, TUNEL, and HE staining and microscopic examination were performed.
[0084] (7) Inhibit lung metastasis of tumor tissue
[0085] The lung samples obtained from the model mice were placed under a stereo microscope and photographed one by one, and the tumor metastases were marked and counted using image J software. Paraffin sections were made from the lung samples, stained with hematoxylin-eosin (HE) staining solution, and examined under a microscope.
[0086] 4. Experimental Results
[0087] (1) Data analysis
[0088] GraphPad Prism 8 software was used for statistical analysis. The data were expressed as mean ± SEM. The t-test (two-tailed) was used for comparison between the two groups. One-way ANOVA was used to evaluate the statistical significance of multiple group analyses. P < 0.05 was considered statistically significant (compared with the control group, *P < 0.05, **P < 0.01, ***P < 0.001, ****P < 0.0001).
[0089] (2) Safety evaluation at the cellular level
[0090] The results of monitoring cytotoxicity by MTT assay showed that the components of the hydrogel precursor had good cell safety. The Live / Dead fluorescence assay was further used to detect the cell viability of cells co-cultured with hydrogel for 1, 3, and 5 days. Figure 4 ), the results showed that the hydrogel had no toxic effect on cells, ensuring that the hydrogel had positive research significance in subsequent experiments.
[0091] (3) Evaluation of therapeutic effects at the cellular level
[0092] The results of the reactive oxygen fluorescence probe method showed that PBCEC can effectively eliminate intracellular reactive oxygen caused by H2O2, maintain the oxygen content of tumor cells, and relieve hypoxia. The results of the 4T1 cell scratch experiment showed that PB / DOX Gel and near-infrared light have the ability to inhibit the migration of 4T1 cells, and PB / DOX Gel+L can significantly inhibit the migration of 4T1 cells, and the results are statistically significant. Finally, we added the corresponding groups of hydrogels to 4T1 cells for co-culture treatment experiments ( Figure 5), we found that in the laser irradiation treatment group, more than half of the cells were killed compared with the control group, which shows that in the absence of chemotherapy drugs, the photothermal conversion efficiency of PB Gel is very high. The PB / DOX Gel group was better than the DOX group. In the PB / DOX Gel+L group, almost all cancer cells were killed. This result shows that PB Gel photothermal has excellent performance and great application potential, and photothermal synergistic chemotherapy shows a more significant killing effect. The above studies on biosafety at the in vitro cell level and treatment at the in vitro cell level confirmed that the PB hydrogel we prepared can be used as a photothermal conversion agent with good biosafety, and has a high research value for photothermal treatment of breast cancer.
[0093] (4) Safety evaluation at animal level
[0094] Within 14 days after the normal BALB / c mice were "treated" according to the groups, there were no abnormalities in the mental state, appetite, behavioral activities, defecation, urination and weight of the mice in each group, and no poisoning or death occurred in any dose group. The weight of the mice increased overall, without a significant decrease, reflecting that the mice in each group were in good health. When the mice were dissected, there were no visible lesions in their hearts, livers, spleens, kidneys, lungs, stomachs and intestines; the organ HE staining observation ( Figure 6 ), showing that the above tissues and organs in the six experimental groups had no pathological damage and were no different from the control group. Based on the above conclusions, the three treatment materials and methods of this study: PB Gel, PB / DOX Gel, and near-infrared photothermal irradiation (L) have good safety for animals.
[0095] (5) Evaluation of therapeutic effects at the animal level
[0096] Photothermal therapy in tumor-bearing mice Figure 7 ), PB Gel+L, and PB / DOC Gel+L showed the strongest temperature increase, indicating that PB Gel can be efficiently enriched and penetrated into the tumor site in mice. After treatment, the therapeutic effect was verified by monitoring the weight of mice and the growth rate of tumor volume ( Figure 8 , 9), and found that the therapeutic effect of PB Gel in the light-exposed group was significantly improved compared with the treatment group without light exposure. Therefore, under light conditions, PB Gel produced a good photothermal effect, which promoted the death of cancer cells. In animal treatment experiments, photothermal therapy (L), DOX, and PB Gel all showed certain effects on inhibiting tumor tissue growth. Staining of tumor tissue sections ( Fig.10 ), macronucleated breast cancer cells were observed in the PBS group, while the number of cells in the PB / DOX Gel+L group was significantly reduced and large areas of cell necrosis appeared. Fig.11, 12), and found that the efficacy of PB / DOX Gel was further improved compared with the use of PB Gel and DOX alone. This shows that the PB Gel carrier enables DOX to achieve a sustained release effect and prolongs the drug action time. Similarly, the efficacy of PB Gel+L is also improved compared with the use of hydrogel and photothermal therapy alone. This shows that PB Gel can effectively convert light energy into heat energy, increase the tissue temperature of photothermal therapy to exceed the tolerance temperature of tumor cells, and achieve the purpose of killing tumor cells. According to statistics, tumor metastasis is the main cause of death in more than 90% of breast cancer patients. The metastatic foci in the lungs were counted, and the tissue morphology was observed by HE staining ( Fig.13 , 14), found that PB / DOX Gel+L can effectively inhibit the lung metastasis of breast cancer tumors. Its inhibitory effect on tumor tissue metastasis was further demonstrated in lung HE staining sections. Above, the combined treatment of Prussian blue loaded doxorubicin hydrogel assisted by photothermal therapy (PB / DOX Gel+L) not only prolongs the drug's action time, improves bioavailability, inhibits tumor tissue growth, but also inhibits tumor lung metastasis, and ultimately effectively treats breast cancer.
[0097] In summary, the present invention provides a Prussian blue chitosan composite hydrogel for chemotherapy-photothermal combined therapy for breast cancer. The efficacy of Prussian blue loaded doxorubicin hydrogel assisted with photothermal therapy was discussed, and its biosafety, tumor inhibition and apoptosis inhibition effect, and ability to inhibit lung metastasis of tumor tissue were confirmed in the treatment of breast cancer. In terms of materials, it is confirmed that Prussian blue hydrogel is a good photothermal converter with biosafety, which can decompose reactive oxygen, improve the hypoxic microenvironment inside the tumor, and then load DOX to improve the ability to promote apoptosis of the tumor. The combined treatment of Prussian blue loaded doxorubicin hydrogel assisted with photothermal therapy can be injected non-invasively into the lesion while maintaining the long-term drug concentration in the tumor site, improving the bioavailability of the drug, and increasing the degree of T cell infiltration in the tumor site of patients with low immunogenic tumors, thereby improving the efficacy of the drug, and minimizing toxic side effects, decomposing endogenous H2O2 into O2, alleviating the hypoxic tumor microenvironment, and releasing the anticancer drug DOX, which is used for effective breast cancer photothermal chemotherapy. The preparation method of the present invention is simple and clear, the preparation conditions are easy to meet, and batch production is easy to achieve.
[0098] It should be noted that the above-mentioned technical contents of the present invention are only for explanation and clarification to enable those skilled in the art to understand the technical essence of the present invention, so the technical contents are not used to limit the substantial protection scope of the present invention. The substantial protection scope of the present invention shall be subject to the claims. Those skilled in the art should know that any modification, equivalent substitution and improvement based on the substantial spirit of the present invention shall be within the substantial protection scope of the present invention.
Claims
1. Application of a Prussian blue / chitosan / sodium alginate composite hydrogel in the preparation of a drug system for treating breast cancer, the preparation method of the Prussian blue / chitosan / sodium alginate composite hydrogel comprising the steps of in-situ polymerization of chitosan with Prussian blue and compounding with sodium alginate; the step of in-situ polymerization of chitosan with Prussian blue comprises first modifying chitosan with carboxyethylation and then polymerizing with Prussian blue; in the step of compounding with sodium alginate, sodium alginate is prepared into polyaldehyde sodium alginate, and then the Prussian blue / chitosan complex obtained in the previous step is compounded with the polyaldehyde sodium alginate to obtain an imine bond cross-linked Prussian blue / chitosan / sodium alginate composite hydrogel; the polyaldehyde sodium alginate is oxidized sodium alginate; and the drug is doxorubicin.
2. The use according to claim 1, characterized in that The chitosan in-situ polymerization of Prussian blue comprises the following steps: suspending 3-6 g of chitosan in 100-300 mL of deionized water, adding 5-6 mL of acrylic acid, and magnetically stirring at 40-60° C. for 2-5 days; adjusting the pH value to 10.0-12.0, dialyzing with deionized water, and the dialyzed molecular weight Mw=6-8 KD; freeze-drying to obtain carboxyethyl chitosan; preparing a hydrochloric acid solution of carboxyethyl chitosan, adding a hydrochloric acid solution of potassium ferrocyanide, heating at 60-80° C. to adjust the pH value to 9.0-11.0, dialyzing with deionized water, and the dialyzed molecular weight Mw=6-8 KD; and freeze-drying to obtain a modified Prussian blue / chitosan complex.
3. The use according to claim 2, characterized in that The step of in-situ polymerization of Prussian blue by chitosan comprises the following steps: (1) Weigh 4 g of chitosan and suspend it in 200 mL of deionized water. Add 5.84 mL of acrylic acid and stir under magnetic stirring at 50 °C for 3 days. (2) Using 1 mol / L sodium hydroxide solution to adjust the pH to 10.0-12.0, dialyze against deionized water for 3 days, and the dialyzed molecular weight Mw = 6-8KD; freeze-dry the dialyzed solution to obtain carboxyethyl chitosan; (3) Prepare 5.0 mL of 2 wt % carboxyethyl chitosan hydrochloric acid solution, add 2.5 mL of hydrochloric acid solution containing 0.5 wt % potassium ferrocyanide, vortex mix, heat in a 70 °C constant temperature electric heating box for 4 h, adjust the pH to 9.0-11.0, dialyze against deionized water for 3 days, and the dialyzed molecular weight Mw = 6-8 KD; the hydrochloric acid concentration used is 6-7 wt %; (4) The dialyzed solution is freeze-dried to obtain a modified Prussian blue / chitosan complex.
4. The use according to claim 1, characterized in that 3-5 wt% of Prussian blue / chitosan composite and 4-6 wt% of oxidized sodium alginate are compounded in a volume ratio of 1-2:1-2 to obtain a composite hydrogel with a solid content of 7-11 wt%.
5. The use according to claim 4, characterized in that 4 wt% Prussian blue / chitosan composite solution was compounded with 5 wt% oxidized sodium alginate solution in a volume ratio of 1:1 to obtain a composite hydrogel with a solid content of 9 wt%.
Citation Information
Patent Citations
Sodium nitroprusside-conjugated medicine-carrying prussian blue analogue nano-photothermal therapeutic agent and preparation method thereof
CN108785673A
KR20210020228A